The Role of Technology in Urban Fragmentation - Wahda Shuker Al-Hinkawi; Vian Abdul Baseer Mohammed (Iraqi Journal of Architecture and Planning, 2018)
The research deals with one of the most important issues that faces cities during their growth, the â€œUrban Fragmentationâ€, which occurs to the city and its parts during its various stages of growth due to many different reasons , technology is one of the most important of those reasons.The research has defined the urban fragmentation as: The state of dismantling, losing coherence, and heterogeneity in urban form and structure, that is linked to the process of city growth, the state of urban fragmentation occurs on different levels such as the formal, spatial, functional and social levels, due to technological developments and functional and economical needs, in addition to the changes in the cultural values and political circumstances.The research problem was determined as: the lack of sufficient knowledge about the role of the information and communication technologies in the fragmentation of cities. The research goal identified as : exploring the phenomenon of urban fragmentation and the most important indicators at the level of form and structure, and define the role of information and communication technology in the fragmentation and re-shaping and structuring the cities.Research has come to build a comprehensive overall vocabulary and indicators to designate the phenomenon of urban fragmentation at formal and spatial , functional and social levels, the main vocabulary of shape and structure was specified for the case study and its secondary vocabulary of the urban fabric, land use and spatial organization of the road grid. By testing the research hypothesis at the Rasafah-Baghdad and Jersey , due to different phases of technological development, the two cities passed through, and the phenomenon of fragmentation as a result of technological progress and development at various stages, at the formal and structural level, the research has come to the most important conclusions of the following:1. The level of fragmentation is varying due the technology in cities form and structure over time.2. The new centralities in contemporary cities caused by the techniques of communication and information are centralities of re- link of the land uses, which was fragmented by the industrial revolution, at the same time it represents a new level of fragmentation at another level of formal and social development of the city.